A new species of Notogalumna from the canopy and another new edaphic species of Galumnopsis (Acari: Oribatida: Galumnoidea) from the tropical rainforest of Los Tuxtlas, Mexico - Villagomez, Fernando; Palacios-Vargas, José G.; Páez, Jair (Zootaxa, 2021)
The genus Galumnopsis (Galumnellidae) is recorded for the first time from Mexico with a new species described here, and Notogalumna (Galumnidae), represents a second record for the country, also with a new species; both from the tropical rainforest in Veracruz state. Notogalumna rickiglesiasi sp. nov. lives in the canopy, while Galumnopsis andydoreyae sp. nov. inhabits soil and litter of Guarea glabra and Astrocaryum mexicanum; most likely they are not only restricted to these plants but are distributed in this forest on a continuous stratum across canopy (Notogalumna) or soil (Galumnopsis). A key for the species of each genus is included.